The Effectiveness of the Government to Government (G2G) Model Through SISKEUDES - Choiriyah, Ilmi Usrotin; U.B, Ahmad Riyadh; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2023)
Government to Government (G2G) is a two-way delivery of information from the government and the government. One form of G2G in the village environment is through the SISKEUDES application. The purpose of this study is to determine the effectiveness of Government to Government through the Siskeudes application using four indicators, namely adaptability, target achievement, job satisfaction and responsibility. This research use desciptive qualitative approach. The analysis technique used is the Miles and Huberman model. The data sources in this study are primary data sources, namely interviews with informants and secondary data sources with photographs or documentation or documents obtained while in the field. The informants for this study were the Village Head, Village Secretary and SISKEUDES application operational apparatus (key informants). The research results show that the use and operation of the SISKEUDES application has been running according to the targets and responsibilities assigned. But in terms of human resources is still minimal. In addition, job satisfaction is still not felt due to the difference in honorarium received with existing regulations.